Primary extrauterine cystic low-grade endometrioid stromal sarcoma mimicking stromal endometriosis. A case report emphasizing the differential diagnosis and its potential local aggressive behavior - Stolnicu, Simona; Tunde, Csilip; Szilard, Gabos; Podoleanu, Cristian; Rozsnyai, Francisc (Polish Journal of Pathology, 2020)
Genital and pelvic endometriosis is a frequently encountered lesion and its importance rely on associated symptoms and its propensity for malignant transformation. In the present paper we comment on the importance of correctly diagnose the malignant transformation of an endometriotic lesion into a cystic low-grade endometrial stromal sarcoma, which is a very rare event. Moreover, we discuss the ability of a low-grade endometrial stromal sarcoma to locally recurr and the differential diagnosis with stromal endometriosis, a lesion that is very rare, almost always microscopic and solid.